A sheath-core composite fiber, a method for producing the same, and use thereof
Patent Information
- Application Number
- CN202611310010.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]目前,针对涤纶纱线的性能改进,一般采用单一材料改性手段,如仅对涤纶进行增韧改性,无法实现纱线强度、耐磨性与柔韧性的协同兼顾,往往出现耐磨提升而强度下降,或柔韧性改善而光泽受损的问题;或采用分步法纺丝制备皮芯结构纤维来优化性能,但该工艺流程复杂、制备成本高昂,且皮芯界面结合力不稳定,易出现皮芯分离现象,导致纤维性能波动大,难以实现工业化规模化生产
[0050](1)本发明提供的皮芯复合纤维的皮层中包括涤纶材料和弹性体材料,能够赋予纤维柔韧性、耐折性和染色亲和性,而芯层的聚酰胺材料能够赋予纤维高强度、高耐磨性和尺寸稳定性;
Smart Images

Figure CN122879858A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of spinning yarn technology, specifically relating to a core-sheath composite fiber, its preparation method, and its application. Background Technology
[0002] Guangyun yarn is a polyester yarn made from 100% PET (polyethylene terephthalate) through specific specifications and spinning processes. Due to its unique luster and comfortable feel, it has broad application prospects in the high-end textile field. However, due to its own molecular structure and specification characteristics, this type of yarn has many performance defects, which seriously restricts its industrial application and the improvement of product added value.
[0003] Due to the high rigidity and crystallinity of polyester molecular chains, the yarn has weak energy absorption capacity and insufficient flexibility, making it prone to brittle breakage. Simultaneously, its relatively large monofilament fineness (approximately 25 μm), while giving the yarn a unique luster and feel, also results in extremely poor abrasion resistance in the fabric. Abrasion tests show that this type of yarn breaks after only 10 revolutions, failing to meet the durability requirements of practical use. To improve the abrasion resistance of polyester yarn, current technologies often employ high-filament multifilaments, reducing the monofilament fineness to enhance the abrasion resistance of both the yarn and the fabric. However, this method sacrifices the unique luster and feel of the polyester yarn itself.
[0004] Currently, the performance improvement of polyester yarn generally adopts single material modification methods, such as only toughening polyester. This cannot achieve a synergistic balance of yarn strength, abrasion resistance and flexibility. Often, abrasion resistance is improved but strength is reduced, or flexibility is improved but luster is damaged. Alternatively, step-by-step spinning is used to prepare core-sheath structure fibers to optimize performance. However, this process is complex, the preparation cost is high, and the core-sheath interface bonding is unstable, which easily leads to core-sheath separation. This results in large fluctuations in fiber performance and makes it difficult to achieve industrial-scale production.
[0005] Therefore, there is a need to provide a fiber that can combine excellent abrasion resistance, flexibility, low-temperature folding resistance, and excellent dyeing properties to meet application requirements. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a core-sheath composite fiber, its preparation method, and its applications.
[0007] To achieve this objective, the present invention employs the following technical solution:
[0008] In a first aspect, the present invention provides a core-sheath composite fiber, comprising a sheath layer and a core layer, wherein the sheath layer is composed of polyester material and elastomer material, and the core layer is composed of polyamide material.
[0009] The core-sheath composite fiber provided by this invention includes polyester material and elastomer material in the sheath layer, which can endow the fiber with flexibility, folding resistance and dyeing affinity, while the polyamide material in the core layer can endow the fiber with high strength, high abrasion resistance and dimensional stability. Thus, the core-sheath composite fiber provided by this invention has excellent abrasion resistance, flexibility, low temperature folding resistance and excellent dyeing performance, which can solve the technical bottleneck of light-colored yarn being not abrasion resistant.
[0010] Preferably, the polyamide material described in this invention is a composite material of polyamide 66 and polyamide 6. Polyamide 66 imparts high strength and high abrasion resistance to the fiber, while the introduction of polyamide 6 can improve the flexibility and dyeing affinity of the blend. The synergistic effect of the two gives the core layer excellent mechanical properties and processing performance. Therefore, it can further improve the abrasion resistance, flexibility, low-temperature folding resistance and dyeing performance of the core-sheath composite fiber.
[0011] Preferably, based on the total mass of the skin layer as 100%, the mass percentage of the polyester material is 70-90%, for example, 70%, 72%, 75%, 78%, 80%, 85%, 88%, 90%, or any of the above values, and the mass percentage of the elastomer material is 10-30%, for example, 10%, 12%, 15%, 20%, 25%, 28%, 30%, or any of the above values.
[0012] This invention enables composite fibers to possess excellent flexibility, folding resistance, and dyeing affinity by controlling the amount of polyester and elastomer materials added to the skin layer. If the amount of elastomer material added is too low, the flexibility and folding resistance of the composite fibers will be poor; if the amount of elastomer material added is too high, the strength of the composite fibers will be significantly reduced.
[0013] Preferably, the number-average molecular weight of the polyester material is 13,500-18,500, for example, 13,500, 14,000, 14,500, 15,000, 15,500, 16,000, 16,500, 17,000, 17,500, 18,000, 18,500 or any of the above values, and preferably the intrinsic viscosity is 0.65-0.80 dL / g, for example, 0.65 dL / g, 0.70 dL / g, 0.72 dL / g, 0.75 dL / g, 0.78 dL / g, 0.80 dL / g or any of the above values.
[0014] Preferably, the elastomer material comprises a polyester thermoplastic elastomer, and more preferably TPEE.
[0015] This invention preferably uses TPEE as an elastomer material, which exhibits excellent compatibility with polyester materials, avoiding the introduction of compatibilizers. Simultaneously, TPEE can form hydrogen bonds with the modified polyamide 66 material, increasing the interfacial adhesion between the skin and core layers, thus preventing the skin-core separation defect during application. The modified polyamide 66 material is a blend of PA66 and PA6, with the preferred PA66:PA6 mass percentage blending ratio being 70:30 (other than preferred ratios, including but not limited to, for example, 60:40, 65:35, 75:25, 80:20, or any range between the above values).
[0016] Preferably, with the diameter of the core-sheath composite fiber as 100%, the thickness of the sheath layer accounts for 20-40%, for example, 20%, 25%, 30%, 32%, 35%, 38%, 40%, or any of the above values.
[0017] If the sheath layer is too thin, it will affect the flexibility, folding resistance, and dyeing affinity of the composite fiber; if the sheath layer is too thick, it will result in a smaller core diameter, affecting the strength, abrasion resistance, and dimensional stability of the composite fiber.
[0018] Preferably, the average diameter of the core-sheath composite fiber is 0.05-0.1 mm, for example, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.1 mm or any of the above values.
[0019] Preferably, the intrinsic viscosity of the polyamide material is ≥2.8 dL / g, for example, 2.8 dL / g, 3.0 dL / g, 3.2 dL / g, 3.5 dL / g, 3.8 dL / g, 4.0 dL / g, or any of the above values.
[0020] The present invention preferably uses high-viscosity polyamide materials, which have excellent fiber-forming properties, high strength, good wear resistance and excellent dimensional stability.
[0021] Preferably, the polyamide material includes polyamide 66 and / or modified polyamide 66, and more preferably, the modified polyamide 66 is a composite material of polyamide 66 and polyamide 6.
[0022] Preferably, the preparation method of the modified polyamide 66 includes: drying polyamide 66 and polyamide 6, then melt-blending and granulating them using a twin-screw extruder; the twin-screw extruder has an aspect ratio L / D ≥ 48, for example 48, 50, 52, 55 or any value between the above, a processing temperature of 250-270℃, for example 250℃, 255℃, 260℃, 265℃, 270℃ or any value between the above, and a screw assembly with medium shear.
[0023] Preferably, the particle size of the polyamide 6 dispersed phase in the modified polyamide 66 is 1-3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or any of the above values.
[0024] Preferably, based on the total mass of the modified polyamide 66 as 100%, the mass percentage of the polyamide 66 is 60-80%, for example, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, or any of the above values.
[0025] This invention utilizes modified polyamide 66 material, which has high strength, high wear resistance and excellent dimensional stability, but relatively insufficient flexibility. The introduction of PA6 can improve the flexibility and dyeing affinity of the blended material, and the synergistic effect of the two makes the core layer have excellent comprehensive performance.
[0026] This invention ensures the excellent performance of the core-sheath composite fiber by limiting the percentage content of polyamide 66 and polyamide 6. If the amount of polyamide 6 added is too large, it may lead to insufficient abrasion resistance of the core-sheath composite fiber; if the amount of polyamide 6 added is too small, the dyeing affinity of the fiber may be poor.
[0027] Preferably, the method for preparing the modified polyamide 66 includes:
[0028] S1. Polyamide 66 and polyamide 6 are dried separately, preferably by vacuum drying. The vacuum drying temperature is preferably 80-90°C, for example 80°C, 83°C, 85°C, 87°C, 90°C or any of the above values, and the drying time is 8-12 hours, for example 8 hours, 9 hours, 10 hours, 11 hours, 12 hours or any of the above values. More preferably, the moisture content after drying is ≤0.08%, for example 0.01%, 0.03%, 0.05%, 0.07%, 0.08% or any of the above values, which can avoid the disadvantage of excessive moisture content caused by the hygroscopicity of PA66 and PA6.
[0029] S2. After drying, the mixture is melt-blended and granulated using a twin-screw extruder to obtain the modified polyamide 66 material.
[0030] Preferably, in the twin-screw extruder, the length-to-diameter ratio L / D is ≥48, for example, 48, 52, 56, 60, 64 or any of the above values; the processing temperature along the barrel is 250-270°C, for example, 250°C, 255°C, 260°C, 265°C, 270°C or any of the above values; and the screw assembly is of medium shear, which can ensure that the particle size of the PA6 dispersed phase is controlled within 1-3 μm (for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or any of the above values).
[0031] The mechanism by which modified polyamide 66 (a blend of PA66 and PA6) significantly improves fiber flexibility, low-temperature folding resistance, and dyeing affinity is as follows:
[0032] On the one hand, the introduction of PA6 disrupts the regular arrangement of PA66 molecular chains, reduces the crystallinity of the blend system, and increases the proportion of amorphous regions. The increased proportion of amorphous regions makes it easier for molecular chain segments to undergo conformational adjustments under stress, thereby giving the material a higher elongation at break (from about 24% of pure PA66 to 28-32%). At the same time, the increase in amorphous regions provides more diffusion channels and binding sites for dye molecules, resulting in a significant increase in dye uptake from about 85% of pure PA66 to over 90%.
[0033] On the other hand, by controlling the length-to-diameter ratio (L / D≥48), processing temperature (250-270℃), and medium-shear screw combination of the twin-screw extruder, the particle size of the PA6 dispersed phase can be precisely controlled within the range of 1-3 μm, forming a uniform "island structure" in the PA66 continuous phase. When the fiber is subjected to low-temperature bending or tensile forces, the uniformly distributed micron-sized PA6 particles can act as stress concentration points, effectively dispersing and dissipating the local stress concentration generated under the action of external forces, thereby inhibiting the initiation and propagation of cracks and preventing cracks from expanding into macroscopic fractures. As a result, the low-temperature flexural endurance has increased from approximately 170,000 cycles for pure PA66 to over 200,000 cycles without fracture.
[0034] This invention achieves a synergistic balance between high strength (≥5.0 cN / dtex) and high flexibility (elongation at break ≥25%) in the core material simply by controlling the physical blending process. It can obtain a core-sheath composite fiber with excellent abrasion resistance, folding resistance and dyeability without the introduction of additional chemical grafting or comonomers.
[0035] In a second aspect, the present invention provides a method for preparing core-sheath composite fibers as described in the first aspect, the method comprising:
[0036] The sheath-core composite fiber is obtained by melt extrusion, cooling and shaping, and drawing and setting of a sheath material comprising polyester and elastomer materials and a core material comprising polyamide materials using a screw extruder.
[0037] This invention obtains the core-sheath composite fiber through a one-step spinning process combined with cooling molding and drawing and setting. The preparation method is simple and easy to implement, and the resulting composite fiber has excellent interfacial bonding between the sheath and core layers, making it less prone to core-sheath separation and other defects.
[0038] In this invention, the melt extrusion includes melting the skin material and the core material separately using a screw extruder, and then extruding them through a composite spinneret.
[0039] Preferably, the cooling and forming method includes air-cooled ring-blowing cooling and / or side-blowing cooling, and more preferably includes a combination of air-cooled ring-blowing cooling and side-blowing cooling.
[0040] Preferably, the air velocities of the air-cooled annular cooling and the side-blowing cooling are each independently selected from 0.4-0.8 m / s, for example, 0.4 m / s, 0.5 m / s, 0.55 m / s, 0.6 m / s, 0.7 m / s, 0.8 m / s or any of the above values.
[0041] This invention utilizes a cooling method that combines air-cooled ring blowing and side blowing to ensure uniform curing of the core-skin structure.
[0042] Preferably, the total draw ratio of the drawing and shaping is 3-5 times, for example, 3 times, 3.5 times, 3.8 times, 4 times, 4.5 times, 4.8 times, 5 times or any of the above values.
[0043] Preferably, the stretching and setting method includes performing pre-orientation, main stretching, and heat setting sequentially;
[0044] Preferably, the pre-orientation temperature is 60-80°C, for example, 60°C, 65°C, 68°C, 70°C, 75°C, 78°C, 80°C or any of the above values.
[0045] Preferably, the temperature of the main stretching is 90-110℃, for example, 90℃, 95℃, 98℃, 100℃, 105℃, 108℃, 110℃ or any of the above values.
[0046] Preferably, the heat setting temperature is 180-220℃, for example, 180℃, 190℃, 195℃, 200℃, 210℃, 215℃, 220℃ or any range between the above values.
[0047] The drawing and shaping method provided by this invention can effectively eliminate the internal stress of composite fibers and stabilize the fiber morphology.
[0048] Thirdly, the present invention provides an application of the core-sheath composite fiber as described in the first aspect in the preparation of woven fabrics.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] (1) The sheath of the core-sheath composite fiber provided by the present invention includes polyester material and elastomer material, which can give the fiber flexibility, folding resistance and dyeing affinity, while the polyamide material of the core layer can give the fiber high strength, high abrasion resistance and dimensional stability.
[0051] (2) The core-sheath composite fiber provided by the present invention has excellent abrasion resistance, flexibility, low temperature folding resistance and excellent dyeing performance, which can solve the technical bottleneck of the lack of abrasion resistance of the light-colored yarn. Among them, the number of sand abrasion test revolutions is ≥20, preferably >55 revolutions and the yarn does not break; the breaking strength is ≥4.0 cN / dtex, preferably ≥5 cN / dtex; the breaking elongation is ≥17%, preferably above 25%; the number of bending times at -20℃ is ≥100,000 times, preferably 200,000 times and the yarn does not break; and the dyeing rate is ≥80%, preferably ≥90%. Attached Figure Description
[0052] Figure 1 This is a 100x magnified cross-sectional view of the core-sheath composite fiber. Detailed Implementation
[0053] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0054] Unless otherwise specified, the raw materials involved in the following specific embodiments of the present invention are all conventional materials in the art, and can be purchased from commercially available products. Some raw material information is as follows:
[0055] PET-1: Polyester resin with a number average molecular weight of 15,000 (GPC test) and an intrinsic viscosity of 0.60-0.70 dL / g, purchased from Sinopec Yizheng Chemical Fiber Co., Ltd., grade FG604;
[0056] PET-2: Polyester resin with a number-average molecular weight of 17,000 (GPC test) and an intrinsic viscosity of 0.74±0.02 dL / g, purchased from Sinopec Yizheng Chemical Fiber Co., Ltd., grade FG720;
[0057] TPEE: Polyester thermoplastic elastomer, purchased from Toyobo Co., Ltd., brand name Pelprene. ® S1001;
[0058] PA66-1: Polyamide 66 high-viscosity chips, intrinsic viscosity of 3.2 dL / g, purchased from BASF, model SE320;
[0059] PA66-2: Polyamide 66 medium-viscosity chips with an intrinsic viscosity of 2.65 dL / g, purchased from Huafeng Chemical Co., Ltd., model T27;
[0060] PA6: High viscosity polyamide 6 chips with an intrinsic viscosity of 2.8 dL / g, purchased from Zhongjin Nylon, model ZJ2800;
[0061] Modified PA66-1, the preparation method is as follows:
[0062] S1. PA66-1 and PA6 were vacuum dried at 85℃ for 10 h, respectively, and the moisture content of the dried products was ≤0.08%.
[0063] S2. After drying, PA66-1 and PA6 are mixed at a mass ratio of 80:20, and melt-blended and granulated using a twin-screw extruder (length-to-diameter ratio L / D=48, processing temperature along the barrel is 250-270℃, screw combination is medium shear) to obtain modified PA66-1.
[0064] Modified PA66-2: The preparation method is the same as that of modified PA66-1, except that the mass ratio of PA66-1 to PA6 is 60:40.
[0065] Modified PA66-3: The preparation method is the same as that of modified PA66-1, except that the mass ratio of PA66-1 to PA6 is 90:10.
[0066] Modified PA66-4: The preparation method is the same as that of modified PA66-1, except that the mass ratio of PA66-1 to PA6 is 50:50.
[0067] Example 1
[0068] This embodiment provides a core-sheath composite fiber, which consists of a sheath layer and a core layer. The sheath layer comprises 75 wt% PET-1 and 25 wt% TPEE, and the core layer comprises modified PA66-1 high-viscosity chips. The core-sheath composite fiber has a diameter of 0.10 mm and the sheath layer accounts for 30% of the fiber thickness.
[0069] The preparation method is as follows:
[0070] S1. Mix PET and TPEE evenly to obtain a leather mixture;
[0071] S2. The skin layer mixture and the core layer material are melt-extruded using a twin-screw extruder, wherein the extrusion temperature of the skin layer mixture is 275℃ and the extrusion temperature of the core layer material is 285℃;
[0072] S3. After melt extrusion, the material is cooled and shaped using air cooling ring blowing at 0.6 m / s + side blowing at 0.5 m / s.
[0073] S4. The formed composite fiber is sequentially stretched and shaped by passing it through a first roller at 70°C, a second roller at 100°C, and a third roller at 200°C, with a total stretch ratio of 4.2 times, to obtain the core-sheath composite fiber.
[0074] Figure 1 The figure shows a cross-sectional view of the core-sheath composite fiber obtained in Embodiment 1 of the present invention. As can be seen from the figure, the composite fiber obtained by the present invention has a core-sheath structure.
[0075] Examples 2-7
[0076] This embodiment provides a core-sheath composite fiber.
[0077] The difference from Example 1 is that, in this example, modified PA66-1 is replaced with equal amounts of modified PA66-2 (Example 2), modified PA66-3 (Example 3), modified PA66-4 (Example 4), PA66-1 (Example 5), PA66-2 (Example 6), and PA6 (Example 7).
[0078] Example 8
[0079] This embodiment provides a core-sheath composite fiber.
[0080] The difference from Example 1 is that, in this example, the composition of the skin layer includes 80 wt% PET-1 and 20 wt% TPEE.
[0081] Example 9
[0082] This embodiment provides a core-sheath composite fiber.
[0083] The difference from Example 1 is that, in this example, the composition of the skin layer includes 90 wt% PET-1 and 10 wt% TPEE.
[0084] Example 10
[0085] This embodiment provides a core-sheath composite fiber.
[0086] The difference from Example 1 is that, in this example, the composition of the skin layer includes 70 wt% PET-1 and 30 wt% TPEE.
[0087] Example 11
[0088] This embodiment provides a core-sheath composite fiber.
[0089] The difference from Example 1 is that, in this example, the composition of the skin layer includes 95 wt% PET-1 and 5 wt% TPEE.
[0090] Example 12
[0091] This embodiment provides a core-sheath composite fiber.
[0092] The difference from Example 1 is that, in this example, the composition of the skin layer includes 65 wt% PET-1 and 35 wt% TPEE.
[0093] Example 13
[0094] This embodiment provides a core-sheath composite fiber.
[0095] The difference from Example 1 is that in this example, the skin thickness accounts for 20%.
[0096] Example 14
[0097] This embodiment provides a core-sheath composite fiber.
[0098] The difference from Example 1 is that in this example, the skin thickness accounts for 40%.
[0099] Example 15
[0100] This embodiment provides a core-sheath composite fiber.
[0101] The difference from Example 1 is that in this example, the skin thickness accounts for 15%.
[0102] Example 16
[0103] This embodiment provides a core-sheath composite fiber.
[0104] The difference from Example 1 is that in this example, the skin thickness accounts for 45%.
[0105] Example 17
[0106] This embodiment provides a core-sheath composite fiber.
[0107] The difference from Example 1 is that in this example, the cooling and shaping in step S3 is air-cooled ring blowing, and the cooling time is the same as in Example 1.
[0108] Example 18
[0109] This embodiment provides a core-sheath composite fiber.
[0110] The difference from Example 1 is that, in this example, the drawing and shaping method in step S4 includes:
[0111] The formed composite fiber is sequentially stretched and shaped by passing it through a first roller at 70°C and a second roller at 200°C, with a total stretch ratio of 4.2 times, to obtain the core-sheath composite fiber.
[0112] Example 19
[0113] This embodiment provides a core-sheath composite fiber, which consists of a sheath layer and a core layer. The sheath layer comprises 75 wt% PET-2 and 25 wt% TPEE, and the core layer comprises PA66-1 high-viscosity chips. The core-sheath composite fiber has a diameter of 0.10 mm and the sheath layer accounts for 30% of the fiber thickness.
[0114] The preparation method is as follows:
[0115] S1. Mix PET and TPEE evenly to obtain a leather mixture;
[0116] S2. The skin layer mixture and the core layer material are melt-extruded using a twin-screw extruder, wherein the extrusion temperature of the skin layer mixture is 260℃ and the extrusion temperature of the core layer material is 270℃;
[0117] S3. After melt extrusion, cooling and shaping are carried out by air cooling ring blowing at 0.4 m / s + side blowing at 0.8 m / s;
[0118] S4. The formed composite fiber is sequentially stretched and shaped by passing it through a first roller at 60°C, a second roller at 90°C, and a third roller at 220°C, with a total stretching ratio of 3 times, to obtain the core-sheath composite fiber.
[0119] Example 20
[0120] This embodiment provides a core-sheath composite fiber, which consists of a sheath layer and a core layer. The sheath layer comprises 75 wt% PET-1 and 25 wt% TPEE, and the core layer comprises PA66-1 high-viscosity chips. The core-sheath composite fiber has a diameter of 0.05 mm and a sheath layer thickness of 30%.
[0121] The preparation method is as follows:
[0122] S1. Mix PET and TPEE evenly to obtain a leather mixture;
[0123] S2. The skin layer mixture and the core layer material are melt-extruded using a twin-screw extruder, wherein the extrusion temperature of the skin layer mixture is 280℃ and the extrusion temperature of the core layer material is 290℃;
[0124] S3. After melt extrusion, cooling and shaping are carried out by air cooling ring blowing at 0.8 m / s + side blowing at 0.4 m / s;
[0125] S4. The formed composite fiber is sequentially stretched and shaped by passing it through a first roller at 80°C, a second roller at 110°C, and a third roller at 180°C, with a total stretching ratio of 5 times, to obtain the core-sheath composite fiber.
[0126] Example 21
[0127] This embodiment provides a core-sheath composite fiber.
[0128] The difference from Example 1 is that in this example, the TPEE in the skin layer is replaced with PET-TPEE, that is, the composition of the skin layer includes 75 wt% PET-1 and 25 wt% PET-TPEE, and the remaining components (the core layer is modified PA66-1), skin layer thickness (30%), diameter (0.10 mm) and preparation process (melting temperature, cooling wind speed, and stretching ratio) are exactly the same as in Example 1.
[0129] Example 22
[0130] This embodiment provides a core-sheath composite fiber.
[0131] The difference from Example 1 is that in this example, the TPEE in the skin layer is replaced with PET-TPEE, and the ratio of PET to PET-TPEE in the skin layer is adjusted to 80 wt% PET-1 and 20 wt% PET-TPEE. The remaining components (the core layer is modified PA66-1), skin layer thickness (30%), diameter (0.10 mm) and preparation process are the same as in Example 1.
[0132] Comparative Example 1
[0133] This comparative example provides a core-sheath composite fiber.
[0134] The difference from Example 1 is that, in this comparative example, the leather layer is composed of 100% PET and the extrusion temperature of the leather layer is 270°C.
[0135] Comparative Example 2
[0136] This comparative example provides a core-sheath composite fiber.
[0137] The difference from Example 1 is that, in this comparative example, the composition of the dermis is 100% TPEE.
[0138] Comparative Example 3
[0139] This comparative example provides a core-sheath composite fiber.
[0140] The difference from Example 1 is that, in this comparative example, the outer layer is composed of PA66-1, and the core layer is composed of 75 wt% PET-1 and 25 wt% TPEE.
[0141] Performance testing
[0142] The performance of the core-sheath composite fibers provided in the examples and comparative examples was tested using the following methods:
[0143] (1) Abrasion resistance: The abrasion resistance was characterized by the number of abrasion tests. The test method was based on GB / T 21196.3-2007 "Textiles - Martindale Method - Determination of Abrasion Resistance of Fabrics - Part 3: Determination of Mass Loss";
[0144] (2) Breaking strength and elongation at break: The test method refers to GB / T 14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments";
[0145] (3) Low temperature folding resistance: After the sample was placed at -20℃ for 24 h, at -20℃, the sample tension was 2 cN / tex, and it was folded 180° (up and down bending) at a folding rate of 2 times / s. The number of bending times when the surface was damaged was recorded.
[0146] (4) Staining rate: The samples provided in the examples and comparative examples were stained using the following methods:
[0147] CI Disperse Red 60 dye (purchased from Huntsman, brand name Terasil) was selected for staining at a concentration of 2% (owf, based on sample mass). The pH of the staining system was adjusted to 5.0 with acetic acid, and the staining was carried out at 130℃ for 45 min under the condition of controlling the liquor ratio of 1:10. After staining, the sample was washed and dried.
[0148] Staining rate: The staining rate was calculated by measuring the maximum absorbance of the dye solution before and after staining using a UV-Vis spectrophotometer. The formula for calculating the staining rate is as follows:
[0149]
[0150] Wherein, A0 and A1 are the absorbance of the dye solution before and after staining, respectively;
[0151] The test results are as follows:
[0152] Table 1
[0153]
[0154] Through examples and performance tests, it was found that the core-sheath composite fiber provided by the present invention has excellent abrasion resistance, flexibility, low-temperature folding resistance, and excellent dyeing performance, which can solve the technical bottleneck of the lack of abrasion resistance of the original fiber. Specifically, the abrasion test has a rotation number ≥20, a breaking strength ≥4.0 cN / dtex, a breaking elongation ≥17%, and a bending number ≥100,000 times at -20℃, and a dyeing rate ≥80%. Under the preferred technical solution of the present invention, the abrasion test has a rotation number >55 and no yarn breakage, a breaking strength ≥5 cN / dtex, a breaking elongation ≥25%, and no yarn breakage after bending 200,000 times at -20℃, and a dyeing rate ≥90%.
[0155] As can be seen from the comparison between Examples 1 and Examples 2-7, in the core-sheath composite fiber of the present invention, using modified polyamide 66 material as the core layer can further improve the overall performance of the core-sheath composite fiber.
[0156] As can be seen from the comparison between Examples 1 and Examples 8-12, when the content of polyester fiber and elastomer material in the core-sheath composite fiber of the present invention is within the preferred range, the overall performance of the core-sheath composite fiber can be further improved.
[0157] As can be seen from the comparison between Examples 1 and Examples 13-16, when the mass ratio of the sheath to the core layer in the core-sheath composite fiber of the present invention is within the preferred range, the overall performance of the core-sheath composite fiber can be improved.
[0158] As can be seen from the comparison between Example 1 and Example 17, when the intrinsic viscosity of the polyamide material described in this invention is within the preferred range, it can improve the overall performance of the core-sheath composite fiber.
[0159] As can be seen from the comparison between Example 1 and Examples 18-19, the preferred preparation method of the present invention can further improve the overall performance of the core-sheath composite fiber.
[0160] A comparison of Examples 1 and 21-22 shows that when PET-TPEE is used instead of TPEE as the skin elastomer material, although the elongation at break and low-temperature flexural strength decrease slightly, the tensile strength is slightly improved, and the abrasion resistance (>55 revolutions) and dyeing rate (≥90%) remain at the excellent levels of this invention. This indicates that PET-TPEE and TPEE have equivalent toughening and modification effects in the system described in this invention, and both can effectively solve the technical bottleneck of the lack of abrasion resistance in Guangyun yarn. Those skilled in the art can flexibly select the above-mentioned elastomer materials according to raw material costs and processing windows.
[0161] As can be seen from the comparison of Example 1 and Comparative Examples 1-3, only the core-sheath composite fiber with the structure defined in this invention can meet the application requirements.
[0162] The present invention has been illustrated through the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A core-sheath composite fiber, characterized in that, It includes a skin layer and a core layer. The skin layer is composed of polyester material and elastomer material, and the core layer is composed of polyamide material.
2. The core-sheath composite fiber according to claim 1, characterized in that, Based on the total mass of the leather layer being 100%, the mass percentage of the polyester material is 70-90%, and the mass percentage of the elastomer material is 10-30%.
3. The core-sheath composite fiber according to claim 1 or 2, characterized in that, The number-average molecular weight of the polyester material is 13,500-18,500, and the preferred intrinsic viscosity is 0.65-0.80 dL / g.
4. The core-sheath composite fiber according to any one of claims 1-3, characterized in that, The elastomer material includes polyester thermoplastic elastomers, preferably including TPEE and / or PET-TPEE.
5. The core-sheath composite fiber according to any one of claims 1-4, characterized in that, With the diameter of the core-sheath composite fiber as 100%, the thickness of the sheath layer accounts for 20-40%; And / or, the average diameter of the core-sheath composite fiber is 0.05-0.1 mm.
6. The core-sheath composite fiber according to any one of claims 1-5, characterized in that, The intrinsic viscosity of the polyamide material is ≥2.8 dL / g; And / or, the polyamide material includes polyamide 66 and / or modified polyamide 66, preferably the modified polyamide 66 is a composite material of polyamide 66 and polyamide 6.
7. A method for preparing a core-sheath composite fiber as described in any one of claims 1-6, characterized in that, The preparation method includes: The outer layer material, which includes polyester and elastomer materials, and the core layer material, which includes polyamide materials, are melted separately, extruded through a composite spinneret, and then cooled, shaped, and stretched to obtain the outer-core composite fiber.
8. The preparation method according to claim 7, characterized in that, The cooling and forming method includes air-cooled ring-blowing cooling and / or side-blowing cooling, preferably a combination of air-cooled ring-blowing cooling and side-blowing cooling; Preferably, the air velocities of the air-cooled annular cooling and the side-blowing cooling are each independently selected from 0.4-0.8 m / s.
9. The preparation method according to claim 7 or 8, characterized in that, The draw ratio for the stretching and shaping is 3-5 times; Preferably, the stretching and setting method includes performing pre-orientation, main stretching, and heat setting sequentially; Preferably, the pre-orientation temperature is 60-80°C; Preferably, the temperature of the main drawing is 90-110℃; Preferably, the heat setting temperature is 180-220℃.
10. The use of a core-sheath composite fiber as described in any one of claims 1-6 in the preparation of woven fabrics.